2004
DOI: 10.1177/1054773804263165
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered Model of Care for Hospital Discharge

Abstract: Patient-centered care is a key characteristic of quality health care in the 21st century. Three patient-driven processes of care, characteristic of patient-centered models of care, may be related to improved readiness for discharge: patients' knowledge of their home-going needs, their relative importance, and their active involvement in the discharge process. Forty-four patients having planned abdominal surgery were interviewed at three time points to determine their information needs and preference for involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 35 publications
3
111
0
1
Order By: Relevance
“…65,71 Knier and colleagues suggested that healthcare providers often inundate patients with information at discharge "in a rushed last minute method without careful planning…" or without consideration of individual patient's needs. 65 (Page 31) Pharmacists remarked that it was not unusual to face competition for patients' time and attention at the time of discharge by many different healthcare professionals who also needed to discuss post discharge care with patients.…”
Section: Competing For Patient's Time At Dischargementioning
confidence: 99%
“…65,71 Knier and colleagues suggested that healthcare providers often inundate patients with information at discharge "in a rushed last minute method without careful planning…" or without consideration of individual patient's needs. 65 (Page 31) Pharmacists remarked that it was not unusual to face competition for patients' time and attention at the time of discharge by many different healthcare professionals who also needed to discuss post discharge care with patients.…”
Section: Competing For Patient's Time At Dischargementioning
confidence: 99%
“…investigated the information desired by patients before discharge, primarily via surveys or qualitative interviews. 3,4,44 In our study, participants expressed a desire for specific details about worrisome clinical signs or symptoms and findings that prompt additional evaluation. Interventions designed to address informational needs and gaps identified by caregivers may improve feelings of discharge readiness and perceived preparation for transition home.…”
Section: Figurementioning
confidence: 99%
“…The way information is provided is very important though, and the resources used can help to apprehend its contents and enhance satisfaction with the process (14)(15) .…”
Section: Resultsmentioning
confidence: 99%